2023
DOI: 10.1037/aap0000296
|View full text |Cite
|
Sign up to set email alerts
|

Promoting pride but missing the need for preparation for bias: Racial-ethnic socialization among Indian American families living in the southeast U.S.

Abstract: Indian Americans are an under researched population within the racial-ethnic socialization (RES) literature, and very little is known about how Indian American immigrant families navigate these conversations. To fill this gap in the literature, the present study explored parent and youth perspectives of RES processes in Indian American families. A total of six focus groups were conducted with 13 adolescents (mean age = 13.6; 60% girls) and 15 parents (mean age = 42.0; 62% mothers). Inductive thematic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 64 publications
0
18
2
Order By: Relevance
“…Since they did not grow up in the U.S. context and are likely less aware of the racial dynamics in the country, they may feel less competent than their U.S.‐born counterparts in advising their children to use strategies such as confrontation or standing up for themselves. Indeed, one qualitative study found that Indian immigrant parents reported sending messages to their teens to ignore discrimination, laugh it off, or avoid thinking about it (Patel et al., 2023). In interviews with Latinx immigrant parents, Ayón (2016) found that parents sent both active and avoidant coping socialization messages.…”
Section: Discussionmentioning
confidence: 99%
“…Since they did not grow up in the U.S. context and are likely less aware of the racial dynamics in the country, they may feel less competent than their U.S.‐born counterparts in advising their children to use strategies such as confrontation or standing up for themselves. Indeed, one qualitative study found that Indian immigrant parents reported sending messages to their teens to ignore discrimination, laugh it off, or avoid thinking about it (Patel et al., 2023). In interviews with Latinx immigrant parents, Ayón (2016) found that parents sent both active and avoidant coping socialization messages.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies documented other ERS strategies in AAPI families, such as egalitarianism (French et al, 2013;Kiang et al, 2022;Kim, Hunt, et al, 2023;Patel et al, 2022), pluralism (Kiang et al, 2022;Kim, Hunt, et al, 2023;Ren et al, 2022), minimization of race (Keum et al, 2023;Kiang et al, 2022;Kim, Hunt, et al, 2023), exposure to diversity (Alvarez et al, 2006;Park, 2020;Tian, 2023), avoidance of race talk (Keum et al, 2023) ERS with other constructs: discrimination (Ajayi & Syed, 2014), ethnic-racial identity (Wu et al, 2020;Xie et al, 2021), American identity (Wu et al, 2020), and model minority experiences (Kiang et al, 2019;Xie et al, 2021).…”
Section: Extent and Nature Of Ersmentioning
confidence: 99%
“…Drawing from these models, we propose that parental RES messages, adolescent experiences with discrimination, race-related messages and conversations from peers, media, and schools that immigrant Asian American and Latinx adolescents receive influence the development of their critical consciousness (Diemer et al, 2015); together, these processes drive adolescents to talk to their parents about potential discriminatory experiences, race in the United States, and about the experiences of other racial groups in the United States. For example, a qualitative study on RES in Indian American families found that when a parent faced discrimination (e.g., told to go back to where they came from), the adolescent asked the parents to retort by asking the “are you fully American?” question (Patel et al, 2022). The adolescent continues to inform the parent about the immigration history of the United States.…”
Section: Integrated Model Of Adolescent-directed Res (Adres)mentioning
confidence: 99%
“…Parents clearly serve as deliverers of cultural messages emanating from the country of origin where they were raised, but they may feel less confident to provide messages about the broader U.S. American context. Indeed, immigrant parents often hesitate to have conversations about race and discrimination because it might be uncomfortable for them (Ayón & García, 2019; Young et al, 2021), because they might not understand the racial hierarchy of the United States (Young et al, 2021), and/or because they feel as though the concepts (i.e., racism and discrimination) are ambiguous (Patel et al, 2022). Immigrant parents may therefore not be delivering messages around discrimination and race, potentially leaving room for adolescent-driven messages.…”
Section: Integrated Model Of Adolescent-directed Res (Adres)mentioning
confidence: 99%
See 1 more Smart Citation